A systemic study of biofuels in complex agriculture markets - Hilbert, Jorge Antonio (Etaflorence, 2021)
During the last decade a great growth in biofuel industry all over the world has occurred. The last few years this tendency has severely changed due to new rules and pressure over the public questioning the sustainability of biofuels and their capability to achieve environmental and social solutions. In general opinions and articles were based on incomplete studies lacking a systemic and holistic view of biofuels within agriculture markets all over the world. The industry is now days in severe danger working at a low rate or closing. In this paper a systemic approach is followed looking for real impact of this industry within very complex markets were co-products are a key factor. Results are based on traceable and public figures comparing them with forecast and projections made by equilibrium models all over the word. Results are based on a complete transformation chain analysis of Argentina case as the first biodiesel exporter country until 2012 and one of the main actors in agricultural commodity markets. Prices, energy and carbon emittions balances are considered over real case studies covering different biofuels and feedstock’s. The results confirm that forecast consequences are very far from real markets and land use behavior. Carbon emitions of first and second generation biofuels need to be revised and closely look at in order to compare them in a fair way.